PENGARUH PUPUK NANOSILIKA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KAPAS (GOSSYPIUM HIRSUTUM L. VAR. KANESIA 8) - Atin Temon Sari; Sri Widodo Agung Suedy; Sri Haryanti (Jurnal Akademika Biologi, 2017)
Cotton (Gossypium hirsutum L.) is one of agricultural commodity which produces natural fiber as a raw material for the textile industry has a lot of constraints in its cultivation which not optimal, so the improvement of cultivation techniques by performing a balanced fertilizer can be done. Indonesian agricultural soil generally has low fertility rate and silica availability, so silica fertilization would be necessary. Silica causes leaves and stems of plant become upright so the photosynthesis will increased. Nanosilica that contains very small elements of silica which makes it easily absorbed by plants in order to increase growth and yield of cotton. This research aims to determine the effect of nanosilica fertilizer to the growth and production and also to know the effective amount of nanosilica concentration which will increase it of cotton Kanesia 8. The study design was using RAL with 5 different treatments of nanosilica fertilizer amount: 0 ml/L, 2.2 ml/L, 4.2 ml/L, 6.2 ml/L dan 8.2 ml/L with 5 repetitions. The data analysis was using ANOVA and if there is a significantly different then the analysis followed by further test of Duncan's Multiple Range Test (DMRT) at 95% of significance level. The results showed that nanosilica fertilizer with a concentration 2.2 ml/L increased the plant growth mainly at fresh weight of plant by 74.62% and dry weight of plant by 33.66% and it also increased the production of plant mainly in the percentage of fruit changed into cotton by 19.71% and dry weight of cotton by 0.98% than the control treatment.Keywords: nanosilica, growth, production, Gossypium hirsutum